Pembuatan Program Aplikasi Berbasis Website Pada Panti Sosial Bina Netra Cahaya Bathin - Maryono Maryono; Zyad Rusdi (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Social institutions Bina Netra Cahaya Bathin is a social institution belonging to the Department of Social Jakarta that provide social welfare services to persons with visual impairments. The purpose of this thesis is to design and implement a social home activities website using PHP and mySQL, where the website can be used for the provision of information up-to-date on the activities of students and admissions existing social institutions, in order to become more effective and efficiently.Designing web-based application program on social institutions Bina Netra Cahaya Bathin system is designed using Microsoft Windows 7 with the PHP programming language and MySQL as database software. With the web-based application program is expected to help social institutions in processing and data storage student so that the system can run relatively more effective and efficient so that it can help improve the performance of social institutions. Keywords:Information Systems, Social institutions Bina Netra Cahaya Bathin, website